Children Social Interaction Changes As A Result Of ‘Tiktok’ Influence - Mazidah, Nur Insyafiatul (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
Nowadays, the influence of social media among children is increasing, especially the use of TikTok Application. The excessive use of it creates apathetic behaviour in the family or in the society. Since children is a fast imitator in copying someone words, behaviours and sociable style, parents should be aware of children social interaction changes due to the inappropriate use of TikTok. The research purpose is to describe children social interaction changes due to the influence of TikTok. Descriptive qualitative was used in the research. Data were gathered through observation, interview, and documents. The research result is children tend to use TikTok excessively because parents are unwise to control the use of smartphone on children.